Change and resilience in Swiss newspapers and broadcasting, 2002 and 2022: Towards a critique of media concentration indices - Riccardo Ferrigato; Petra Mazzoni; Benedetta Prario; Gabriele Balbi (Communication & Society (Formerly Comunicación y Sociedad))
This paper examines and compares the Swiss broadcasting and newspaper markets in 2002 and 2022, before and after digitalization transformed traditional media markets. It analyses differences and continuities over the two decades, the loss of relevance of national companies, and the increasing weight of foreign companies. Also, it focuses on the dynamics of media concentration and proposes a comparative historical approach to better capture its mutations over time and its impact on pluralism.